2023
DOI: 10.3390/jof9020232
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Association between YEASTONE Antifungal Susceptibility Tests and Clinical Outcomes of Cryptococcus Meningitis

Abstract: The relation between antifungal susceptibility and treatment outcomes is not well-characterized. There is paucity of surveillance data for cerebrospinal fluid (CSF) isolates of cryptococcus investigated with YEASTONE colorimetric broth microdilution susceptibility testing. A retrospective study of laboratory-confirmed cryptococcus meningitis (CM) patients was conducted. The antifungal susceptibility of CSF isolates was determined using YEASTONE colorimetric broth microdilution. Clinical parameters, CSF laborat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
(28 reference statements)
1
2
0
Order By: Relevance
“…Similar to our results, a study conducted in patients with cryptococcal meningitis reported a higher mortality in patients with AMB non‐WT (40%) compared with patients with AMB WT (22.8%) isolates receiving AMB‐containing regimens 40 . Another study in patients with cryptococcal meningitis demonstrated higher mortality in patients with cryptococcal isolates with elevated MICs for AMB and FLC, especially when patients had an isolate with FLC MIC of greater than 64 mg/L 41 . In contrast, other studies have shown no difference in outcomes.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Similar to our results, a study conducted in patients with cryptococcal meningitis reported a higher mortality in patients with AMB non‐WT (40%) compared with patients with AMB WT (22.8%) isolates receiving AMB‐containing regimens 40 . Another study in patients with cryptococcal meningitis demonstrated higher mortality in patients with cryptococcal isolates with elevated MICs for AMB and FLC, especially when patients had an isolate with FLC MIC of greater than 64 mg/L 41 . In contrast, other studies have shown no difference in outcomes.…”
Section: Discussionsupporting
confidence: 89%
“…40 Another study in patients with cryptococcal meningitis demonstrated higher mortality in patients with cryptococcal isolates with elevated MICs for AMB and FLC, especially when patients had an isolate with FLC MIC of greater than 64 mg/L. 41 In the treatment of severe forms of cryptococcosis, the relevance of an elevated MIC to a single antifungal agent may be diminished by the frequent utilisation of combination antifungal therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Mortality due to cryptococcosis among patients co-infected with HIV and treated with amphotericin B and fluconazole was not associated with MIC data, indicating low resistance rates from 0% to 5.8% for C. neoformans and C. gattii , respectively [ 60 , 101 , 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 , 126 , 127 , 128 ]. Therefore, in general, we need a better way to evaluate the in vitro correlation with clinical response to therapy [ 62 , 121 , 129 ].…”
Section: Clinical Outcome: the Role Of Antifungal Susceptibility Testingmentioning
confidence: 99%